Economics of water resources - Spulber, Nicolas (Kluwer Academic, 1997)
The Second Edition of Economics of Water Resources: From Regulation to Privatization updates and expands the exposition of the authors' central theses concerning: 1. the integration of water quantity--quality issues, and the treatment of water as a multi-product commodity, with the market playing the major role in the determination of water quality--discrimination pricing; 2. the drawbacks of public control, regulation and enforcement, and the need to expand privatization of water supply and of water and wastewater treatment facilities to ensure their appropriate, adequate, development and modernization through increased reliance on private capital; 3. the unification and centralization of water management at river basin level in order to handle effectively the expanding pressures for water availability, for the evaluation of waterborne disease, for extensive and effective pollution abatement as well as for coping with the related issues of soil erosion, siltation in streams, channels and reservoirs, protection against stress from drought and floods, and with myriad problems relating to the environment, recreation and navigation. While expanding and updating the underlying data, the authors maintain the basic division of the book into four parts